Booth’s Algorithm Design Using Field Programmable Gate Array - Ab Hadi, Nik Azran; A Aziz, Khairul Azha; Hashim, Nik Mohd Zarifie; Omar, Muhammad Shukri; Jaafar, Anuar (IJARET, 2014)

(untitled)
Nowadays,digital device is very important to all people in this world. The high speed operation and less space and energy required had made the digital devices more preferred.This project is to design digital system which performed fixed point Booth Multiplier Algorithm where the design system would be developed using hardware description language (HDL),in this case,VHDL (VHSIC Hardware Description Language),VHSIC stands for Very High Speed Integrated Circuit.In this project would be used Xilinx ISE 10.1which is the software used to designed digital system for Xilinx manufactured FPGA board.In Xilinx have two main languages which are VHDL and Verilog.For design Booth’s Multiplier Algorithm we used Verilog code which is has to create the program module and test bench.In that case,to design digital system will have input and output which is input is 8 bits and output is 16 bits.Finally, it is proven that the system created can calculate and yield a fixed point multiplied output of the input value.